Antifungal potential of Rhinacanthus nasutus extracts against the pathogenic fungus Cryptococcus neoformans - Muthita Khongthongdam; Trinity Jantarach; Tanaporn Phetruen; Sittinan Chanarat (PLoS ONE, 2025)
Rhinacanthus nasutus (snake jasmine) has been widely used in Thai-traditional medicine to treat various ailments, including fungal infections. This study aimed to investigate the antifungal activity of R. nasutus extracts and their impact on the virulence factors of Cryptococcus neoformans , a pathogenic yeast responsible for cryptococcal infections in immunocompromised individuals. Extracts were prepared from the leaves, roots, and a combination thereof, with rhincanthin-C quantified using High-Performance Liquid Chromatography (HPLC). Antifungal activity was assessed using a spot assay against Saccharomyces cerevisiae and C. neoformans . The root extract demonstrated the strongest antifungal effect, particularly against C. neoformans . Further investigation into virulence factors revealed a noticeable reduction in melanin production, cell and capsule sizes and alterations in cell structure, suggesting cellular abnormality. The findings of this study demonstrate the antifungal potential of R. nasutus and may warrant future exploration of its therapeutic applications for treating fungal infections.